Antimicrobial photodynamic therapy against Propionibacterium acnes biofilms using hypericin (Hypericum perforatum) photosensitizer: in vitro study - Barroso, Rosmeire Aparecida (2020)
Acne vulgaris is the most recurring skin condition in the world, causing great harm to the physical and psychological well-being of many patients. Antimicrobial photodynamic therapy (aPDT) has broad therapeutic applicability. The purpose was to evaluate in vitro the photodynamic inactivation against Propionibacterium acnes (P. acnes) biofilms by using different concentrations of hypericin (Hypericum perforatum) photosensitizer associated with different energies of low-level laser. The biofilms were placed in 96-well microplates with a 6.4-mm diameter surface, by using standard suspensions (2 × 107 CFU/mL) and grown in brain heart infusion broth (BHI) for 48 h in anaerobic chamber. Subsequently, the control group received application of 0.9% sterile saline solution for 3 min; the photosensitising groups received hypericin at concentrations of 5 and 15 μg/mL for 3 min; the laser groups received irradiation of energies of 3 and 5 J (660 nm, continuous output, 100 mW, 30 and 50 s and 100 J/cm2 and 166 J/cm2, respectively); the aPDT groups received 5 and 15 μg/mL concentrations of hypericin associated with energies of 3 and 5 J of low-level laser irradiation. After the biofilms were broken up and seeded for CFU counting. The results showed a reduction in P. acnes biofilms after aPDT emphasising that 15 μg/mL hypericin associated with 3 and 5 J laser irradiation reduced biofilms by 14.1 and 27.9%, respectively. In addition, all groups of aPDT demostrated statistically significant reductions. In vitro photodynamic inactivation against P. acnes biofilms using different concentration of hypericin photosensitizer associated with different energies of low-level laser promoted effective antimicrobial action.